Analysis of the Effectiveness of Zakat Collection, Management, and Distribution in Improving Social Welfare in Indonesia - Hasiun Budi; Muhammad Irwan; Robby Kurniawan; Nur Awwalunnisa; Loso Judijanto (West Science Islamic Studies, 2024)
This research explores the effectiveness of Zakat collection, management, and distribution in improving social welfare in Indonesia, employing a sample of 250 participants and utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS). The measurement model analysis demonstrates robust loading factors, reliability, and convergent validity, while the discriminant validity analysis confirms the distinctiveness of the latent constructs. In the structural model, positive and statistically significant relationships are found between the effectiveness of Zakat distribution, collection, management, and the improvement of social welfare. The R-square and adjusted R-square values of 0.602 and 0.592, respectively, indicate a strong explanatory power of the model. These findings underscore the transformative potential of Zakat in addressing socio-economic disparities and contribute valuable insights for policymakers and practitioners in the field of social development.